HUBUNGAN STATUS PERKAWINAN, APOE ε4, DAN JENIS AKTIVITAS FISIK TERHADAP PENURUNAN KOGNITIF PADA LANSIA PEREMPUAN - Nicholas Andrian Singgih; Yuda Turana; Yvonne Suzy Handajani; Nelly Tina Widjaja; Linda Suryakusuma (PERDOSNI, 2019)
RELATIONSHIP OF MARITAL STATUS, APOE ε4, AND TYPES OF PHYSICAL ACTIVITIES ON COGNITIVE DECLINE IN ELDERLY WOMENABSTRACTIntroduction: The number of elderly population in Indonesia continues to increase every year, especially women. Elderly women are at higher risk of experiencing decreased cognitive function.Aims: To determine the relationship between the characteristics of the subject, vascular risk factors, APOE ε4 genotype, and the type of physical activity with the decline of cognitive function in elderly women.Methods: A cognitive cohort study of 114 elderly women who had been observed for a mean of ±2.5 years, as part of the Active Aging study at Atma Jaya Catholic University. The independent variables of this study included were age, education, marital status, vascular risk factors (hypertension, diabetes, dyslipidemia, and BMI), APOE ε4, and types of physical activity. Cognitive function is measured using Mini Mental State Examination (MMSE).Results: There were 114 subjects with mean age was 71.22±7.297 and 33.3% experienced a decline in cognitive function. There were 114 subjects with mean age was 71.22±7.297 and 33.3% experienced a decline in cognitive function. Age, marital status (single), and type of physical activity (cooking) have a significant relationship with Relative Risk (RR) of 4,45; 0,12; and 0,334.Discussions: Factors related to cognitive decline in elderly women were age. Marital status (single) and cooking activities were protective factors.Keywords: APOE, cognitive decline, elderly, marital status, physical activityABSTRAKPendahuluan: Angka populasi lansia di Indonesia setiap tahunnya terus meningkat, terutama perempuan. Lansia perempuan berisiko lebih tinggi mengalami penurunan fungsi kognitif.Tujuan: Mengetahui hubungan antara karakteristik subjek, faktor risiko vaskuler, genotip APOE ε4, dan jenis aktivitas fisik terhadap penurunan fungsi kognitif pada lansia perempuan.Metode: Penelitian kohort terhadap 114 lansia perempuan >60 tahun yang diikuti fungsi kognitifnya selama rerata ±2,5 tahun, sebagai bagian dari penelitian Active Aging di Universitas Katolik Atma Jaya. Variabel bebas penelitian ini meliputi usia, pendidikan, status perkawinan, faktor risiko vaskuler (hipertensi, diabetes, dislipidemia, dan IMT), APOE ε4, dan jenis aktivitas fisik. Fungsi kognitif diukur menggunakan Mini Mental State Examination (MMSE).Hasil: Didapatkan 114 subjek dengan rerata usia 71,2±7,3 dan 33,3% mengalami penurunan fungsi kognitif. Analisis multivariat menunjukkan usia, status perkawinan (single) , dan jenis aktivitas fisik (memasak) memiliki hubungan bermakna dengan risiko relatif (RR) masing-masing 4,46; 0,12; dan 0,334.Diskusi: Faktor risiko gangguan fungsi kognitif pada lansia perempuan adalah usia. Status perkawinan (single) dan aktivitas memasak merupakan faktor protektif.Kata kunci: Status perkawinan, APOE, aktivitas fisik, penurunan kognitif, lanjut usia